Effects of The Covid 19 Pandemic and The Problems of Corporate Bankruptcy - Izabela EMERLING (Communications of International Proceedings, 2021)
In recent years, there has been a sharp increase in the number of reported bankruptcies, both domestically and internationally, due to the pandemic crisis. Bankruptcies are observed not only among companies entering the market, but more and more often also among large enterprises. The aim of the article is to present and analyze the theoretical and practical aspects of bankruptcy of enterprises, the impact of the corona virus pandemic on the economies of countries, and to identify whether covid 19 significantly contributed to the increase in bankruptcy of enterprises in Europe and Poland. The applied research methods are based on the study of the literature on the subject as well as the comparison method and analysis performed. For this  purpose, comparative analysis methods and tools were used. The main research objective of the article is to investigate and compare the number of bankruptcies in companies in Europe and Poland in the years preceding the crisis caused by the pandemic and in 2020 during covid 19, as well as to assess the impact of the pandemic on the increase in corporate bankruptcies. The basic research hypothesis is: The covid 19 crisis contributed to spectacular corporate bankruptcies. The verification of the above research hypothesis is the main goal of this article.
Keywords: Bankruptcy; Covid 19; Pandemic; Enterprises; Countries' Economies.